Estudo da diversidade química e genética de Eugenia spp. no Estado de Sergipe - Santos, Lucas Barbosa dos (2018)
The state of Sergipe holds several species of the genus Eugenia, which are popularly known as uvaia. Species of this genus have been disappearing, mainly due to the lack of management strategies for native forests exploitation and agricultural and urban expansion. Thus, the study of chemical and genetic diversity has been used as an essential tool that allows recognizing the species that need conservation priorities, or that can be selected in a breeding program, besides helping to detect other medicinal potentialities. The objective of this study was to analyze the chemical diversity of essential oils and the genetic characterization of native populations of uvaia plants (Eugenia spp.) in the state of Sergipe. The chemical analyses were performed using GC/MS/FID, and genetic analyses were carried out using the ISSR marker (Inter-Simple Sequence Repeat). Thirty compounds were identified in the essential oils, which were distributed within the chemical groups, regardless the species and collection site. The clustering analysis revealed four groups Group 1, consisting of four plants, was characterized by having α-copaenoe (19.06-22.91%), (E)-caryophyllene (17.58-21.37%), germacrene D (11.55-14.28%), and δ-cadinene (9.01-11.17%) as major compounds. Group 2, consisting of 11 plants, presented δ-elemene (2.60-21.18%), germacrene D (6.58-22.13%), and/or bicyclogermacrene (0-26.36%) as major compounds. Group 3, consisting of nine plants, was characterized by the presence of spathulenol (18.09-49.61%) and/or (E)-β-elemenone (0-30.15%) and muurola-4,10 (14) -dien-1-β-ol (5.58-13.35) as major compounds. Group 4, consisting of seven plants, presented spathulenol (2.68-25.62) and (E)-β-elemenone (35.21-49.05%) as major compounds. In the molecular analyses, the genetic diversity of Nei (He) ranged from 0.25 to 0.29, with a mean value of 0.27 between the different Eugenia species. The Shannon index (I) ranged from 0.37 to 0.44, with a mean of 0.40. The UPGMA method (unweighted pair group method with arithmetic mean) revealed two groups of plants, with an evident separation between the two species, which were classified as Eugenia selloi (O.Berg) B.D. Jacks and Eugenia subreticulata Glaz. The genetic clustering proved to be different from the chemical clustering. Genetic diversity within each species can be considered as low and indicates the urge for the development of plant conservation strategies. The individual analysis of the chemical diversity of the essential oils of the species formed three chemical groups in Eugenia subreticulata and two chemical groups in E. selloi.